Acceptance and Willingness to Pay for Vaccine Against Human Papilloma Virus (HPV) Among Parents of Boys in Central Vietnam - Nguyen, Lan Hoang; Le, Thuy Bich Thi; Le, Nhu Quynh Nguyen; Tran, Nhan Thanh Thi (Frontiers in Public Health, 2022)
Human papilloma virus (HPV) vaccine for adolescents was recommended as an effective prevention strategy of HPV-related cancers. In Vietnam, HPV vaccination has not been introduced to male adolescent. This study was conducted to examine the acceptance of having boys vaccinated against HPV and its underlying reasoning, and to identify their parent's willingness to pay (WTP) for HPV vaccination in central Vietnam. 785 parents of boys were directly interviewed based on a structured questionnaire. Parent's acceptability of HPV vaccine for their sons was identified by one question with response on 3-point scale (agree, don't know, and disagree). Multivariate logistic regression model was used to determine contributing factors to participant's acceptance. Bidding game method was applied to elicit WTP values for HPV vaccination with initial bid of 161.2 USD. The results showed that 49.2% of parents agreed to have their sons vaccinated against HPV. Factors that influenced parent's acceptance including son's age older than 12 years (OR = 1.5; 95% CI: 1.08–1.98); being eldest son (OR = 1.6; 95% CI: 1.13–2.19), being mother (OR = 1.4; 95% CI: 1.01–1.91), parents with high educational level (OR = 1.7; 95% CI: 1.11–2.47) and their knowledge of HPV and HPV vaccine (OR = 1.8; 95% CI: 1.23–2.65). Average WTP value for full doses of HPV vaccine was 137.5 USD, ranging between 9 USD and 188.3 USD. Parents' knowledge of HPV and HPV vaccine was the only factor affecting WTP value (Rho: 0.11; p-value: 0.030). The findings suggest a strategy be introduced for HPV vaccination to male adolescents in Vietnam.